Banana fiber/low-density polyethylene recycled composites for third world eco-friendly construction applications – Waste for life project Sri Lanka - Bolduc, S; Jung, K; Venkata, P; Ashokcline, M; Jayasinghe, R; Baillie, C; Lessard, L (My University, 2018)
In the framework of the waste for life Sri Lanka project, low value industrial low-density polyethylene waste plastics and banana fibers made from agricultural waste are upcycled into affordable eco-friendly building products. This creates income for the local communities while mitigating waste disposal and reducing ecological problems. Within this context, a robust manufacturing method using compression molding was developed. Panels with varying fiber content were manufactured using unchopped and chopped fibers. Low-density polyethylene characterization using Fourier transform infrared spectroscopy and differential scanning calorimetry to compare plastic sources was conducted. To reduce cost, no fiber treatments or compatibilizers were used. An estimate of critical fiber length was found to be around 1.45 cm to 2.5 cm. A trend of increasing strength with fiber content (up to 40 wt.%) was achieved by using longer fibers than in the previous research. Handling and dispersion of the fibers were increased by chopping the fibers to 20 cm lengths, which led to an increase in tensile strength due to easier manufacturing. Cross-ply panels made with fibers chopped to a length of 20 cm were found to be strongest peaking at around 40 wt.% with a tensile strength of 32.8 MPa, a fourfold increase compared to a raw low-density polyethylene (0 wt.%) panel.
Keywords: Low-density polyethylene, banana fiber, waste for life, natural fiber composite, mechanical properties, recycled waste composite